2013
DOI: 10.1126/science.1239560
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the CO Snow Line in a Solar Nebula Analog

Abstract: Planets form in the disks around young stars. Their formation efficiency and composition are intimately linked to the protoplanetary disk locations of "snow lines" of abundant volatiles. We present chemical imaging of the carbon monoxide (CO) snow line in the disk around TW Hya, an analog of the solar nebula, using high spatial and spectral resolution Atacama Large Millimeter/Submillimeter Array observations of diazenylium (N2H(+)), a reactive ion present in large abundance only where CO is frozen out. The N2H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
324
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(362 citation statements)
references
References 51 publications
(37 reference statements)
33
324
5
Order By: Relevance
“…The depletion of CO and H 2 O in the quiescent phase thus allows N 2 H + to increase in abundance at almost all radii for the first few 1000 yr after the burst. This type of anti-correlation between CO and N 2 H + is well known from observations of molecular clouds, embedded protostars, and circumstellar disks (Bergin et al 2002;Jørgensen 2004;Qi et al 2013) and was also noted by Lee (2007). On timescales of more than a few 1000 yr, freeze-out of N 2 near 400 AU causes a decrease in the N 2 H + abundance.…”
Section: Abundance Profilesmentioning
confidence: 84%
“…The depletion of CO and H 2 O in the quiescent phase thus allows N 2 H + to increase in abundance at almost all radii for the first few 1000 yr after the burst. This type of anti-correlation between CO and N 2 H + is well known from observations of molecular clouds, embedded protostars, and circumstellar disks (Bergin et al 2002;Jørgensen 2004;Qi et al 2013) and was also noted by Lee (2007). On timescales of more than a few 1000 yr, freeze-out of N 2 near 400 AU causes a decrease in the N 2 H + abundance.…”
Section: Abundance Profilesmentioning
confidence: 84%
“…This selective freeze-out of major ice reservoirs can change the overall elemental [C]/[O] abundance ratio in the gas and thus the composition of the atmospheres of giant planets that are formed there 94 . The CO snowline has been imaged with ALMA through N 2 H + observations in the nearby TW Hya disk 233 . N 2 H + is enhanced when its main destroyer, CO, freezes out.…”
Section: Protoplanetary Disksmentioning
confidence: 99%
“…through dust growth) but are also relevant for the final composition of bodies formed in the disk. Recently Qi et al (2013) reported the imaging of the CO snowline in the TW Hya disk via observations of the N 2 H + ion. N 2 H + is efficiently destroyed by proton transfer to CO…”
Section: Ice Linesmentioning
confidence: 99%
“…Surface chemistry processes produce complex molecules on the dust surface (e.g. hydrogenation of CO to form H 2 CO, Qi et al 2013), and these molecules may subsequently be photo-desorbed. One prominent example for this suggested formation process is methanol (Walsh et al 2010;Dutrey et al 2014).…”
Section: Chemical Structurementioning
confidence: 99%